(untitled) (Fiep Bulletin - online, 2015)
The drug abuse is a public health problem that affects people of all ages, in all societies, with biopsychosocial consequences that need to be discussed nationally and internationally. In Brazil, it is estimated that 9% of the population is chemically dependent. In this context, the present study has as main objective to analyze the acute effects of exercise in controlling the level of anxiety and mood among a group of people participating in a Rehabilitation Center Drug in the city of Teresina, PI. The research is quantitative using the comparative method. The study population consisted of 35 recovering addicts at the center for psychosocial care Alcohol and other drugs (CAPS-AD), but only 22 people had their data analyzed. In the survey, was used as an instrument of data collection, a questionnaire to characterize the sample and two tests, one to measure the level of anxiety (STAI-E) and the second to assess the mood of individuals (Scale of humor of BRUMS). The tests were administered before and after exercise on days 9, 10 and July 13, 2014. The test results when compared before and after demonstrated that there was a decrease in the number of individuals with anxiety. In the mood were observed positive results in all subscale means. However, when analyzing the data in a statistical way it was perceived that there was no significant results on mood state. It is concluded that exercise has had a positive effect on anxiety and mood of drug addicts. Therefore, the exercise can be considered an additional tool in the treatment of drug addicts.